2019
DOI: 10.1007/s10815-019-01598-4
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting debates of premature luteinization and its effect on assisted reproductive technology outcome

Abstract: The impact of the prematurely elevated serum progesterone on the late follicular phase, commonly known as premature luteinization (PL), is a matter of continuing debate. Available evidence supports that serum progesterone ≥ 1.5 ng/ml on the day of ovulation triggering could reduce the pregnancy potential in fresh in vitro fertilization (IVF) cycles by jeopardizing endometrial receptivity. Causes of PL during ovarian stimulation are unclear. Recent studies point toward the daily follicle-stimulating hormone dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…In particular, when serum P4 levels were > 1.75 ng/mL, the rates of GQE at the cleavage stage were significantly reduced. Some analyses have indicated that there is a significant association with a decreased probability of pregnancy during IVF cycles with detrimental endometrial receptivity under a serum P4 threshold > 1.5 ng/mL [ 17 , 18 , 19 ]. However, the clinical criteria for increased P4 levels are highly dependent on individual clinics [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when serum P4 levels were > 1.75 ng/mL, the rates of GQE at the cleavage stage were significantly reduced. Some analyses have indicated that there is a significant association with a decreased probability of pregnancy during IVF cycles with detrimental endometrial receptivity under a serum P4 threshold > 1.5 ng/mL [ 17 , 18 , 19 ]. However, the clinical criteria for increased P4 levels are highly dependent on individual clinics [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of premature progesterone rise (PPR) during the late follicular phase in 1991, there has been considerable interest in the past 30 years [ 1 ]. PPR is generally defined as serum progesterone ≥ 1.2 ng/mL or ≥1.5 ng/mL on the day of the hCG trigger in controlled ovarian stimulation cycles [ 2 , 3 , 4 ]. This phenomenon is relatively common in in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) procedures, with an incidence rate of approximately 17–29% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Premature luteinization is defined as an early elevation of circulating P4 in the late follicular phase, measured prior to or on the day of hCG trigger in women receiving ovarian stimulation for IVF (51,52). It often causes a cancellation of fresh embryo transfer due to the risks of altered endometrial receptivity and embryo-endometrial asynchrony, which result in lower implantation and pregnancy success (52)(53)(54)(55)(56). High doses of FSH have been postulated as a major reason for the high P4 secretion (57), but the underlying mechanisms remain unknown.…”
mentioning
confidence: 99%